HeartMate 3 biventricular support exceeding 4.5 years - Hrvoje Gasparovic; Davor Milicic; Kristina Krželj; Maja Hrabak Paar; Tomislav Kopjar; Nina Jakus; Ivo Planinc; Maja Cikes (ESC Heart Failure, 2023)
Abstract A 47‐year old male with ischaemic cardiomyopathy was referred to us for durable left ventricular assist device placement. He was found to have prohibitively elevated pulmonary vascular resistance for heart transplantation. He underwent HeartMate 3 left ventricular assist device implantation, with additional temporary right ventricular assist device (RVAD) placement. Following a 2‐week period of unweanable temporary right ventricular support, the patient was switched to durable biventricular support with two Heartmate 3 pumps. The patient was placed on a transplant waiting list but was not offered a heart for over 4 years. While on Heartmate 3 biventricular support (BiVAD), he returned to full activity and enjoyed an excellent quality of life. He underwent laparoscopic cholecystectomy 7 months after the BIVAD implant. After 52 months of uneventful BiVAD support, he presented with a combination of adverse events that occurred over a short period. These included subarachnoidal haemorrhage and a new motor deficit, followed by RVAD infection and RVAD low‐flow alarms. After over 4 years of unimpeded RVAD flows, new imaging revealed an outflow graft twist with subsequent flow reduction. The patient underwent heart transplantation after a total of 1655 days of Heartmate 3 BiVAD support and continues to do well on latest follow‐up.